Design of Magnetron Cooling Method Based on Heat Exchanger System for Microwave Heating Application - Gerry Sasanti Nirmala; Doddy Abdassah; Erdilla Indriyani; Anugerah Solida; Sudjati Rachmat; Taufan Marhaendrajana; Achmad Munir (Journal of Engineering and Technological Sciences, 2022)
Microwave heating is a novel thermal recovery technique developed for heavy oil reservoirs. Particulary in deep reservoirs, it allows more effective thermal recovery to counter heat loss.. The magnetron as a microwave generator works based on cavity resonant vibrations and it needs an appropriate cooling system to avoid damage to its cavity elements. In this paper, the design of a cooling system based on a heat exchanger as well as the investigation of the proper material and coolant to fit the microwave characteristics are proposed.